Maximal lactate accumulation rate and post-exercise lactate kinetics in handcycling and cycling - Quittmann, O. J.; Abel, T.; Vafa, R.; Mester, J.; Schwarz, Y. M.; Strüder, H. K. (European Journal of Sport Science, 2021)
The aim of this study was to assess lactate kinetics, maximal lactate accumulation rate (V Lamax) and peak power output (POmax) in a 15-s all-out exercise in handcycling (HC) and cycling (C) in terms of (1) reliability, (2) differences and (3) correlations between HC and C.